2009
DOI: 10.1002/jmv.21417
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the novel KI Polyomavirus in paranasal and lung tissues

Abstract: KI is a novel polyomavirus identified in the respiratory secretions of children with acute respiratory symptoms. Whether this reflects a causal role of the virus in the human respiratory disease remains to be established. To investigate the presence of KIV in the respiratory tissue, we examined 20 fresh lung cancer specimens and surrounding normal tissue along with one paranasal and one lung biopsy from two transplanted children. KIV‐VP1 gene was detected in 9/20 lung cancer patients and 2/2 transplanted patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…Following this finding, other body compartments and specimen types have been screened: stool (6,17,23,(46)(47)(48), whole blood (45,48), plasma (18,49,50), serum (49), cerebrospinal fluid (51), lymphoid tissue (16,40,47), urine (6,7,48), and lung tissue (24,52). Detection rates of KIPyV and WUPyV in biological specimens are reported in Tables 1 and 2.…”
Section: Specimens Collectionmentioning
confidence: 99%
“…Following this finding, other body compartments and specimen types have been screened: stool (6,17,23,(46)(47)(48), whole blood (45,48), plasma (18,49,50), serum (49), cerebrospinal fluid (51), lymphoid tissue (16,40,47), urine (6,7,48), and lung tissue (24,52). Detection rates of KIPyV and WUPyV in biological specimens are reported in Tables 1 and 2.…”
Section: Specimens Collectionmentioning
confidence: 99%
“…Little is known about the cell tropism of this virus, but viral sequences are predominantly found in respiratory tract secretions, with prevalence ranging between 0.5 and 6.5 % (Babakir-Mina et al, 2013). KIPyV DNA has occasionally been amplified from paranasal tissue (Babakir-Mina et al, 2009b), tonsil (Babakir-Mina et al, 2009b;Astegiano et al, 2010), lymphoid tissue (Sharp et al, 2009), lung tissue (Babakir-Mina et al, 2009c;Teramoto et al, 2011), stool (Allander et al, 2007;Babakir-Mina et al, 2009a;Bialasiewicz et al, 2009;Kantola et al, 2009;Mourez et al, 2009;Li et al, 2013), brain (Barzon et al, 2009b), eyebrow hair (Hampras et al, 2015), normal skin (Hampras et al, 2015) and blood and plasma (Barzon et al, 2009a;Babakir-Mina et al, 2010;Csoma et al, 2012;Touinssi et al, 2013). Immunohistochemical assay of spleen tissue from a 42-year-old human immunodeficiency virus (HIV)-positive male with a monoclonal antibody against the capsid protein VP1 of KIPyV stained positive, but the identity of the KIPyV VP1-positive cell type could not be determined (Siebrasse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…WUPyV DNA was also detected in cerebral spinal fluid (CSF) of one patient (Barzon et al, 2009b). KIPyV DNA or VP1 protein was found in lung cancer tissue and in alveolar macrophages and spleen (Babakir-Mina et al, 2009;Siebrasse et al, 2014). MCPyV seems to be a common skin commensal (Bellaud et al, 2014;Hampras et al, 2015;Mertz et al, 2013;Schowalter et al, 2010), but DNA is also found in blood, eyebrow hairs, tonsils, gall bladder, intestine, appendix, liver, lung, lymphoid tissue, saliva and oral samples, and urine (reviewed by Baez et al, 2013;Hampras et al, 2015;Signorini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%